FROM THE HISTORY OF ACUTE MESENTERIC OCCLUSION (THE EPOCH OF NEW TIME). Part I - O. Sh. Oynotkinova; A. V. Esipov; M. D. Pacenko; D. A. Mironenko; A. V. Tyschuk (Архивъ внутренней медицины, 2015)
Acute mesenteric occlusions and acute bowel infarction were described in the middle of the nineteenth century. In spite of the achievements of modern medicine acute mesenteric ischemia is still one of the most dangerous pathologies in emergency surgery. This survey covers the historical periods of research of certain aspects of acute infarction of mesenteric circulation, which shaped our modern perception of this disease.